PARAMETRGE BAYLANÍSLÍ ÚShINShI DÁREJELI TEŃLEMELERDI ShEShIWDE GEOMETRIYALÍQ USÍL - Seydullaev, K.X.; Seidullaev, A.K.; Amangeldieva, J.T.; Jumamuratova, A.O. (SCIENCE and SOCIETY, 2025)
In this article, we investigate a geometric method for solving the parameter-dependent equations of a third-degree polynomial with real coefficients.